Polyfunctional KLRG-1+CD57+ Senescent CD4+ T Cells Infiltrate Tumors and Are Expanded in Peripheral Blood From Breast Cancer Patients - Ramello, Maria C.; Núñez, Nicolás G.; Tosello Boari, Jimena; Bossio, Sabrina N.; Canale, Fernando P.; Abrate, Carolina; Ponce, Nicolas; Del Castillo, Andrés; Ledesma, Marta; Viel, Sophie; Richer, Wilfrid; Sedlik, Christine; et al. (Frontiers in Immunology, 2021)
Senescent T cells have been described during aging, chronic infections, and cancer; however, a comprehensive study of the phenotype, function, and transcriptional program of this T cell population in breast cancer (BC) patients is missing. Compared to healthy donors (HDs), BC patients exhibit an accumulation of KLRG-1+CD57+ CD4+ and CD8+ T cells in peripheral blood. These T cells infiltrate tumors and tumor-draining lymph nodes. KLRG-1+CD57+ CD4+ and CD8+ T cells from BC patients and HDs exhibit features of senescence, and despite their inhibitory receptor expression, they produce more effector cytokines and exhibit higher expression of Perforin, Granzyme B, and CD107a than non-senescent subsets. When compared to blood counterparts, tumor-infiltrating senescent CD4+ T cells show similar surface phenotype but reduced cytokine production. Transcriptional profiling of senescent CD4+ T cells from the peripheral blood of BC patients reveals enrichment in genes associated with NK or CD8+-mediated cytotoxicity, TCR-mediated stimulation, and cell exhaustion compared to non-senescent T cells. Comparison of the transcriptional profile of senescent CD4+ T cells from peripheral blood of BC patients with those of HDs highlighted marked similarities but also relevant differences. Senescent CD4+ T cells from BC patients show enrichment in T-cell signaling, processes involved in DNA replication, p53 pathways, oncogene-induced senescence, among others compared to their counterparts in HDs. High gene expression of CD4, KLRG-1, and B3GAT1 (CD57), which correlates with increased overall survival for BC patients, underscores the usefulness of the evaluation of the frequency of senescent CD4+ T cells as a biomarker in the follow-up of patients.